CREATING EFFECTIVENESS OF NUTRITION POLICY IMPROVEMENT PROGRAM IN SUBANG REGENCY - Kusnadi, Iwan (Department of Government, FISIP, Universitas Padjadjaran, 2020)
This study aimed to determine the effectiveness of the nutrition improvement program policy in Subang Regency. This study uses a qualitative descriptive research method through observation and interviews, literature study, and documentation. Data triangulation and obtained from key informants directly and relevant to the problem under study are sources of data. The results showed that the policy program for improving Subang Regency nutrition has been running but has not been effective, including several factors such as limited human resources who manage the program. The availability of additional food for infants and toddlers is still insufficient. For this reason, it needs to be considered so that the program can be carried out properly following the stated objectives. The government needs to pay more attention to the adequacy of nutrition workers. To provide maximum service to the community. The implementation of nutrition improvement programs must be more activated, maintained continuously, and improved communication and socialization, built both cross-program and cross-sectoral to reduce malnutrition cases. Procedures for handling cases of malnutrition. It is hoped that the procedure for referring children suffering from malnutrition can be faster so that children can be treated quickly, and their nutritional condition can quickly improvegb777